THE COMPUTER VISION WORKSHOP develop the skills you need to use computer vision algorithms in your own artificial intelligence projects. - Asad, Hafsa (PACKT PUBLISHING, LIMITED, 2020)
With The Computer Vision Workshop, you'll explore the basic and advanced techniques in video and image processing using OpenCV and Python. It is filled with real-world exercises and activities that will make the learning process easy and enjoyable.